Bronchoscopic Closure of Bronchopleural Fistula with Occluder - Ma M; Xie D; Zhang L; Li M; Meng Q; Xu S; Xing X (Cancer Management and Research)
Mingxi Ma,1,2 Daomin Xie,3 Lihui Zhang,1 Mengli Li,1 Qiu Meng,1,2 Shuanglan Xu,1 Xiqian Xing1 1Department of Pulmonary and Critical Care Medicine, the Affiliated Hospital of Yunnan Medical University, Key Laboratory of Respiratory Disease Research of Department of Education of Yunnan Province, Kunming, 650021, People’s Republic of China; 2Clinical Medical College of Dali University, Dali, Yunnan, 671000, People’s Republic of China; 3Department of Respiratory Medicine, Qiaojia County People’s Hospital, Zhaotong, Yunnan, 654600, People’s Republic of ChinaCorrespondence: Xiqian Xing; Shuanglan Xu, Department of Respiratory Medicine, the Affiliated Hospital of Yunnan University, the Second People’s Hospital of Yunnan Province, Kunming, Yunnan, 650021, People’s Republic of China, Email xingxiqian@ynu.edu.cn; xushuanglan99@163.comAbstract: Bronchopleural Fistula (BPF) represents one of the gravest complications post-lobectomy. Present treatment strategies encompass a wide array of surgical techniques complemented by essential adjunct therapies. Despite numerous treatment modalities, mortality rates associated with BPF remain disconcertingly high. Advances in bronchoscopic technology have led to the widespread adoption of bronchoscopic interventions, celebrated for their safety, minimal invasiveness, and efficacy. The cornerstone of BPF management involves the use of sealants, metal-covered stents, and occlusion devices, with the success of these occlusions critically dependent on the fistula’s dimensions. Particularly for expansive BPFs deemed inappropriate for surgical intervention, metal-covered stents and occlusion devices are frequently favored. This review critically assesses the therapeutic efficacy and clinical utility of metal-covered stents and occlusion devices through a comprehensive analysis of the extant literature. Additionally, it outlines risk stratification and management strategies for BPF, with the intent to furnish novel insights and methodologies for the clinical diagnosis and treatment of this complex condition.Keywords: bronchopleural fistula, bronchoscopy, interventional pulmonology, pneumonectomy, lung cancer